How do you solve #3(-9m + 9) = 5(-m + 45)#?

1 Answer
Jul 14, 2015

Answer:

#m=-9#

Explanation:

We are given #3(-9m+9)=5(-m+45)#

First let's multiply the #3# and the #5# into the parenthesis:

#3(-9m+9)=5(-m+45)#

#3*(-9m)+3*9=5*(-m)+5*45#

#-27m+27=-5m+225#

Let's now add #5m# to both sides:

#-27m+27=-5m+225#

#-22m+27=225#

and then, subtract #27# from both sides:

#-22m+27=225#

#-22m=198#

Now, let's divide both sides by #-22#:

#-22m=198#

#m=-9#

Let's check our answer by plugging in #-9# into #m#:

#3(-9m+9)=5(-m+45)#

#3(-9*(-9)+9)=5(-(-9)+45)#

#3(81+9)=5(54)#

#3(90)=270#

#270=270#